الهجرات الأندلسية إلى طرابلس وبرقة خلال القرنين الخامس عشر والسادس عشر الميلاديين وآثارها الاجتماعية والحضارية - مـريم الصادق جمعة (Scientific Journal of University of Benghazi, 2017)
During The sixteenth and seventeenth centuries, large groups of Andalusian immigrants transmigrated to the Maghreb region. These migrations brought many social and cultural effects. The coastal areas of Tripoli and Berqa (Cyrenica) attracted a number of these immigrants, many of the Andalusian families settled in Tripoli during this period. There were also attempts to settle immigrants from Andalusia in the province of Berqa during the sixteenth century when the Andalusian community settled in the city of Derna, contributed to the prosperity of the city after a long of period of recession , and this research aims to study these migrations and clarify the social and cultural impact on the region, the most important results that can be drawn from this study is the influence of the Andalusian communities that settled in the country on their new society especially in terms of social, where the Andalusian community became an important part of the demographics of some cities during the sixteenth and seventeenth century, such as city of Derna, besides their impact on social customs and tradition. This community also contributed to the development of some aspects of economic life such agriculture and industry and in the revitalization of scientific and culture life, especially in the areas of justice, stupidity, teaching and mysticism, as well as in enriching the artistic life, and spread types of Andalusian arts such as Al-Moshahat .